STUDENTS' PERCEPTIONS OF SPOTIFY: A QUANTITATIVE STUDY OF SMP ISLAM NURUL IMAN - Agustiningrum, Tessana; Susanti, Ani (Universitas Muhammadiyah Metro, 2025)
English pronunciation is a common challenge for Indonesian students, mainly due to the influence of regional accents in Bahasa Indonesia. This research investigates how the lyrical feature of the Spotify application helps students improve their English pronunciation. The study focuses on students of class 8A at SMP Islam Nurul Iman Lampung Timur, chosen based on the researcher’s teaching experience, where students faced difficulties in English pronunciation. The purpose of this study is to explore students’ perceptions of using Spotify lyrics as a tool to enhance their English pronunciation skills. This study employs a descriptive quantitative design. A questionnaire was used as the primary instrument to collect data, tabulated and analyzed descriptively. The results reveal that 95% of students frequently use Spotify, with 60% agreeing and 40% strongly agreeing that the lyrics feature on Spotify significantly helps improve their vocabulary and pronunciation. The findings not only suggest the effectiveness of Spotify's lyrical feature but also inspire optimism about the potential of integrating digital media into language learning to address pronunciation challenges in an engaging and accessible manner.